SINERGI AI (QUILLBOT) DAN BUDAYA BATAK TOBA: UPAYA MENDUKUNG KETERAMPILAN MENULIS BAHASA PRANCIS DENGAN BUKU CERITA DIGITAL - Herman Syahputra; Hadijah Handayani Sibuea; Irda Yusepa; Widya Trisna Handayani; Harun Sitompul (Smart Education, 2026)
Abstract: This study aims to develop a digital storybook based on Batak Toba culture integrated with QuillBot AI as an editing assistant to support students' French writing skills. The study employed a mixed-methods approach using the Educational Design Research (EDR) framework. Data were collected through interviews, observations, expert validation questionnaires, and limited trials. The resulting product was a digital storybook entitled Sahabat Danau Toba, equipped with writing tasks, a French glossary, and a QuillBot-assisted editing feature. Material and media expert validations achieved scores of 94% and 93%, respectively, indicating that the product was highly feasible. The one-to-one, small-group, and field-test evaluations obtained scores of 83.3%, 88%, and 96%, respectively. The overall user response reached 94.3% and was categorized as very good. Students reported that the Batak Toba-based story was interesting, easy to understand, and helpful in generating writing ideas. QuillBot also helped students independently revise their grammar and improve their writing. Therefore, the developed product is feasible as a supporting medium for French writing instruction based on local culture. Keywords: Artificial Intelligence, Batak Toba Culture, Digital Storybooks, Writing Skills, French Language Learning Abstrak: Penelitian ini bertujuan mengembangkan buku cerita digital berbasis budaya Batak Toba yang terintegrasi dengan AI QuillBot sebagai asisten editor untuk mendukung keterampilan menulis bahasa Prancis mahasiswa. Penelitian menggunakan pendekatan mixed methods dengan desain Educational Design Research (EDR). Data dikumpulkan melalui wawancara, observasi, angket validasi ahli, dan uji coba terbatas. Produk yang dihasilkan berupa buku cerita digital Sahabat Danau Toba yang dilengkapi tugas menulis, glosarium bahasa Prancis, dan fitur QuillBot. Hasil validasi ahli materi dan ahli media masing-masing memperoleh skor 94% dan 93% dengan kategori sangat layak. Hasil one-to-one evaluation memperoleh skor 83,3%, small group evaluation 88%, dan field test 96%. Rata-rata respons pengguna mencapai 94,3% dengan kategori sangat baik. Mahasiswa menyatakan bahwa cerita berbasis budaya Batak Toba menarik, mudah dipahami, dan membantu mengembangkan ide menulis. Fitur QuillBot juga membantu mahasiswa memperbaiki tata bahasa dan tulisan secara mandiri. Dengan demikian, produk yang dikembangkan layak digunakan sebagai media pendukung pembelajaran menulis bahasa Prancis berbasis budaya lokal. Kata kunci: Artificial Intelligence, Budaya Batak Toba, Buku Cerita Digital, Writing Skills, French Language Learning